First attempted breeding of Manx Shearwater (Puffinus puffinus Brünnich, 1764) on Santa Maria, Azores - Bried, Joël (2007)
The Manx Shearwater Puffinus puffinus (Brünnich, 1764) is a north Atlantic seabird which mainly breeds in Europe. In the Azores, its breeding colonies occur exclusively on the islands from the western group (Flores and Corvo). Here, we report the first breeding attempt observed on Vila islet, Santa Maria (the easternmost island of the archipelago, situated circa 600 km from Flores and Corvo). Our observation confirms that Manx Shearwaters can settle far from their usual breeding localities and enhances the importance of Vila islet for the Azorean marine avifauna.